Estudo do pré-tratamento com atenolol na musculatura cardíaca de ratos submetidos à isquemia-reperfusão intestinal: análise histológica e bioquímica - Okada, Aparecida Mieko [UNIFESP] (2016)
Purpose: Inflammation has been shown to induce cardiac damage in multiple cardiovascular diseases produced by various insults, including intestinal ischemia-reperfusion. The protective role of atenolol, a beta-1-selective blocker, in myocardial damage after intestinal ischemia/reperfusion is not well understood. Objective: The aim of this study was to evaluate the effects of atenolol as possible cytoprotective drug in myocardial injury by intestinal ischemia - reperfusion in rat model. Materials: Rats were randomly exposed to sham operation, the groups are divided in intestinal ischemia/reperfusion (IR), with saline solution (SS) infusion (SS+IR), and atenolol (AT) infusion and intestinal IR (AT+IR) using atenolol in one and two doses at 2 mg/kg. Results: The results demonstrated that compared of untreated IR group to treated IR groups, AT reduced ventricular wall damage area, serum TNF-? (from SS+IR: 287.42±3.95 pg/ml to AT+IR: 231.28±9.16 pg/ml and AT+I+AT+R : 195.86±13.18 pg/ml, and the level of malondialdehyde (MDA) (MDA = SS+IR: 7.96±0.15 pmol/mg to AT+IR: 5.6±0.14 pmol/mg and AT+I+AT+R: 4.9±0.07 pmol/mg), data expressed in mean ± M. Conclusion: Our research suggested that atenolol reduced cardiac effects against intestinal IR injury in rats, which may be attributed to attenuating inflammation and oxidative stress and ameliorated cardiac dysfunction.